(untitled) (Bangladesh Journal of Animal Science, 2013)
The present study was conducted using records on four breeding bulls maintained at the Artificial Insemination (AI) Center of Bangladesh Agricultural University (BAU), Mymensingh and on 154 of their progeny maintained at BAU Dairy Farm (112) and some villages (42 progeny) adjacent to BAU for estimating the effect of breeding bulls and genetic parameters on early growth performance of the progeny at farm and field levels. Genetic correlations between traits of bulls and their progeny were also estimated. Bull traits were metabolic body weight (MWT), feed intake (FI) and residual feed intake (RFI) where progeny traits were birth weight (BWT), final body weight (FWT) at 90 days of age and average daily gain (ADG). Mean BWT of progeny at farm and field level was 16.34±1.85 to 17.62±1.97 kg and 13.89±2.78 to 16.11±2.98 kg, respectively. The FWT at farm progeny was 48.9±2.87 to 55.67±2.14 kg whereas 43.43±2.50 to 52.22±3.34 kg for field progeny. The ADG at farm and field progeny was 0.36±0.03 to 0.43±0.01 and 0.32±0.03 to 0.42±0.03 kg, respectively. The BWT and FWT of farm progeny were significantly (p>0.05) higher than the progeny of field level. Breeding bulls had significant (p<0.05) effect on FWT and ADG for both of the farm and field progeny. Estimated heritability was found to be moderate in case of BWT (0.32±0.19), but low for FWT (0.26±0.18) and ADG (0.29±0.20) for pooled average. The genetic correlation between bulls MWT and BWT was high (rg=0.54±0.17), but low with FWT(rg=0.26±0.18) and ADG (rg=0.28±0.23). Moderate in daily FI of bulls was genetically correlated with BWT (0.45±0.22), FWT (0.38±0.24) and ADG (0.35±0.25) for their progeny, while low but favorable negative genetic correlation (rg=-0.13±0.17) was observed between ADG of progeny and RFI of bulls. The negative correlation for RFI with ADG suggested that selection might result in better success in improving herd production efficiency without compromising progeny growth performance. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18484 Bang. J. Anim. Sci. 2013. 42 (2): 81-88